Analysis of Food Taboo and Food Belief Compliance in Anemic Pregnant Women at Tuntang Community Health Center - Nabila Fahmi Hidayat; Risky Ika Riani; Yanuarita Tursinawati; Muslimah Muslimah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Anemia in pregnancy is defined as a hemoglobin concentration ≤ 11.0 g/dL. Inadequate diet can be caused by a culture of food taboo and food belief, this causes pregnant women to be at high risk of experiencing anemia. Objective: The aim of this study was to analyze the compliance of anemic pregnant women with food taboos and food beliefs. Methods: This research uses qualitative methods with an ethnological design. This research design was carried out using in-depth interviews. There were 9 research informants, namely 5 pregnant women with anemia and 4 additional informants. Audio recordings were transcribed and analyzed using thematic analysis.Results: The level of compliance of anemic pregnant women at the Tuntang health center towards the culture of food taboo and food disbelief is high. They tend to comply with input regarding intake from the family. Pregnant women who still adhere to this culture admit that they have followed this culture since their first pregnancy. Foods they avoid include goat meat, eggs and papaya leaves. Medical personnel play a role in providing education to pregnant women through routine examinations, classes for pregnant women, and providing additional food. Knowledge of anemic pregnant women at the Tuntang health center is quite good. Conclussion: Food taboo and food belief attitudes and habits are still adhered to due to family influence. They often get nutritional information through advice from medical personnel.